2001
DOI: 10.1103/physrevlett.87.178305
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Flow of a Two-Dimensional Foam under Continuous Shear

Abstract: We investigate the flow properties of a 2D foam (a confined monolayer of jammed bubbles) submitted to a continuous shear in a Couette geometry. A strong localization of the flow at the moving inner wall is evidenced. Moreover, velocity fluctuations measurements reveal self-similar dynamical structures consisting of clusters of bubbles moving coherently. A stochastic model is proposed where bubbles rearrangements are activated by local stress fluctuations produced by the shearing wheel. This model gives a compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
285
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(305 citation statements)
references
References 15 publications
16
285
3
1
Order By: Relevance
“…A key result of this work is the identification of the important role of both the range and strength of the potential in determining the structure of the mechanically stable clusters. First, we found that for N ≥ 6, as the range of the bubble interaction potential decreases from that for the (12,6) potential to that for the short-range "sticky" (30, 50) potential, the clusters tend to possess more gaps between bubble pairs on the periphery of the clusters. In this case, the distinct clusters obtained from simulations using the long-range potential are a better match to those from experiments.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…A key result of this work is the identification of the important role of both the range and strength of the potential in determining the structure of the mechanically stable clusters. First, we found that for N ≥ 6, as the range of the bubble interaction potential decreases from that for the (12,6) potential to that for the short-range "sticky" (30, 50) potential, the clusters tend to possess more gaps between bubble pairs on the periphery of the clusters. In this case, the distinct clusters obtained from simulations using the long-range potential are a better match to those from experiments.…”
Section: Discussionmentioning
confidence: 98%
“…6). We find that the distance in configuration space between each cluster obtained in simulations with long-range attractions (12,6) and the corresponding cluster obtained in experiments satisfies ∆R/σ LL < 0.2, as shown in Fig. 10.…”
Section: Structure Of Mechanically Stable Clustersmentioning
confidence: 91%
See 3 more Smart Citations